2020
DOI: 10.1021/acs.jpca.0c02948
|View full text |Cite
|
Sign up to set email alerts
|

General Method for Determining Redox Potentials without Electrolyte

Abstract: A novel method to determine redox potentials without electrolyte is presented. The method is based on a new ability to determine the dissociation constant, K°d, for ion pairs formed between any radical anion and any inert electrolyte counterion. These dissociation constants can be used to determine relative shifts of redox potential as a function of electrolyte concentration, connecting referenced potentials determined with electrochemistry (with 0.1 M electrolyte) to electrolyte-free values. Pulse radiolysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In nonpolar solvents such as dichloromethane, electrolyte concentration has been shown to dramatically effect measured reduction potentials. , Thus, in our effort to estimate halogen reductions under conditions similar to those where halogen atoms may be generated in photoredox catalysis, , quenching rate constants reported in Table were determined from experiments performed in the absence of an added electrolyte. When charged photocatalysts and halides are used in the absence of a supporting electrolyte, substantial changes to the ionic strength, and therefore the diffusional rate constant, occur throughout the titration.…”
Section: Resultsmentioning
confidence: 99%
“…In nonpolar solvents such as dichloromethane, electrolyte concentration has been shown to dramatically effect measured reduction potentials. , Thus, in our effort to estimate halogen reductions under conditions similar to those where halogen atoms may be generated in photoredox catalysis, , quenching rate constants reported in Table were determined from experiments performed in the absence of an added electrolyte. When charged photocatalysts and halides are used in the absence of a supporting electrolyte, substantial changes to the ionic strength, and therefore the diffusional rate constant, occur throughout the titration.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is known that halide sequestration with affinities of only 10 4 M –1 has led to such significant halide stabilization that they were no longer oxidized by photocatalysts, while freely diffusing halides were still reactive. , This observation has been interpreted as a perturbation to E °′(Χ •/– ) afforded by sequestration that preferentially stabilizes the anionic form of the halogen species. Recent pulse radiolysis studies have shown that even “inert” electrolytes can stabilize redox-active ions by hundreds of millivolts. These examples highlight the need to develop a stronger understanding of how noncovalent interactions affect the kinetics and thermodynamics of electron transfer, and more broadly, any reaction where ion stabilization impacts reactivity. …”
Section: Introductionmentioning
confidence: 99%
“…However, this scenario assumes that there are no stabilizing interactions for the electron-transfer products in the redox equilibrium. This assumption is rarely reasonable in chemistry and biology, yet is the sole contribution considered in time-honored photochemical analysis , and state-of-the-art kinetic measurements. ,, This assumption is particularly problematic in determination of E °′(SG + , Χ •/– ) +/0 as the K eq values do not account for noncovalent interactions with the halogen atom that would be particularly important for polarizable halide ions like iodide. Therefore, experimental methods to determine how ion stabilization through noncovalent interactions impacts formal reduction potentials are critically needed.…”
Section: Introductionmentioning
confidence: 99%
“…While reports of the change in redox potential due to addition of electrolyte are rare, some results from our laboratory became available recently [14,15]. To introduce the concept of shifts of redox potentials, Figure 1 displays potentials for four couples, t-stilbene 0/À ,F 10 0/À , Cocp 2 +/0 , and Fecp 2 +/0 (referred to herein as Fc) in THF over a wide range of concentrations of the electrolyte TBAPF 6 .F 10 is a ten-unit oligomer of 9,9-dihexyl fluorene.…”
Section: What Is the Effect Of Electrolytes On Redox Potentials?mentioning
confidence: 99%
“…In highly polar media such as water or acetonitrile, there is little ion pairing and most electrolyte exists as free ions. Ionic atmospheres around radical anions or cations stabilize them, described as change of their activities, γ, calculated [14] here using extended Debye-Hückel theory. In these calculations in redox potential, the component attributed to activities is usually small.…”
Section: Redox Potential Shifts By Ion Pairing and Activitiesmentioning
confidence: 99%